Comparison of Custodiol® and modified St.Thomas cardioplegia for myocardial protection in coronary artery bypass grafting - Cvetković, Dragan; Kočica, Mladen; Šoškić, Ljiljana; Vučićević, Filip; Petrović, Olga; Jovanović, Ivana; Jovičić, Snežana; Trifković, Jelena; Kostovski, Saša; Miličić, Biljana; Karadžić, Milica; Ristić, Arsen; et al. (Vojnosanitetski pregled, 2020)
Background/Aim. Custodiol® is a hyperpolarizing cardioplegic solution which has been used in our national cardiac surgical practice exclusively for the heart transplant surgery. Owing to its numerous advantages over the standard depolarizing solutions, Custodiol® became cardioplegic solution of choice for all other cardiac surgical procedures in many cardio-surgical centers. This study evaluated myocardial protection by Custodiol® compared to modified St. Thomas cardioplegic solution in coronary artery bypass surgery. Methods. In a prospective four-month study, 110 consecutive adult patients who underwent primary isolated elective on-pump coronary artery bypass grafting (CABG) were randomized into the Custodiol® group (n = 54) and the St. Thomas groupa (n = 50), based on the type of administered cardioplegia; six patients were excluded. Cardiac protection was achieved as antegrade cold crystalloid cardioplegia by one of the solutions. Myocardial preservation was assessed through following outcomes: spontaneous rhythm restoration post cross-clamp, and postpoperative cardiac specific enzymes level, ejection fraction (EF) change, inotropic support, myocardial infarction (MI), atrial fibrillation (AF), and death. Results. Preoperative and intraoperative characteristics of patients in both groups were similar except for a considerably longer cross-clamp time in the Custodiol® group (49.1 ± 19.0 vs. 41.0 ± 12.9 minutes; p = 0.022). The Custodiol® group exhibited a higher rate of return to spontaneous rhythm compared to the St. Thomas group (31.5% vs. 20.0%, respectively; p = 0.267), lower rates of AF (20.4% vs. 28%, respectively; p = 0.496), MI (1.8% vs. 10.0%, respectively; p = 0.075) and inotropic support (9.0% vs. 12.0%, respectively; p = 0.651), albeit not statistically significant. There was an insignificant difference in peak value of troponin I between the Custodiol® and Thee St. Thomas group (5.0 ± 3.92 µg/L vs. 4.5 ± 3.39 µg/L, respectively; p = 0.755) and creatine kinase-MB (26.9 ± 15.4 µg/L vs. 28.5 ± 24.2 µg/L, respectively; p = 0.646) 6 hours post-surgery. EF reduction was comparable (0.81% vs. 1.26%; p = 0.891). There were no deaths in both groups. Conclusions. Custodiol® and modified St.Thomas cardioplegic solution have comparable cardioprotective effects in CABG surgery. The trends of less frequent MI, AF and inotropic support, despite the longer cross-clamp time in the Custodiol® group may suggest that its benefits could be ascertained in a larger study.
Keywords: heart arrest, induced; custodiol-n solution; cardiac surgical procedures; postoperative period; arrhythmias, cardiac; heart function tests; mortality